Neonatal Diabetes and Congenital Hyperinsulinism Caused by Mutations in ABCC8/SUR1 are Associated with Altered and Opposite Affinities for ATP and ADP - Ortiz, David; Bryan, Joseph (Frontiers in Endocrinology, 2015)
ATP-sensitive K+ (KATP) channels composed of potassium inward-rectifier type 6.2 and sulfonylurea receptor type 1 subunits (Kir6.2/SUR1)4 are expressed in various cells in the brain and endocrine pancreas where they couple metabolic status to membrane potential. In β-cells, increases in cytosolic [ATP/ADP]c inhibit KATP channel activity, leading to membrane depolarization and exocytosis of insulin granules. Mutations in ABCC8 (SUR1) or KCNJ11 (Kir6.2) can result in gain or loss of channel activity and cause neonatal diabetes (ND) or congenital hyperinsulinism (CHI), respectively. SUR1 is reported to be a Mg2+-dependent ATPase. A prevailing model posits that ATP hydrolysis at SUR1 is required to stimulate openings of the pore. However, recent work shows nucleotide binding, without hydrolysis, is sufficient to switch SUR1 to stimulatory conformations. The actions of nucleotides, ATP and ADP, on ND (SUR1E1506D) and CHI (SUR1E1506K) mutants, without Kir6.2, were compared to assess both models. Both substitutions significantly impair hydrolysis in SUR1 homologues. SUR1E1506D has greater affinity for MgATP than wildtype; SUR1E1506K has reduced affinity. Without Mg2+, SUR1E1506K has a greater affinity for ATP4- consistent with electrostatic attraction between ATP4-, unshielded by Mg2+, and the basic lysine. Further analysis of ND and CHI ABCC8 mutants in the second transmembrane and nucleotide binding domains (TMD2 & NBD2), found a relation between their affinities for ATP (± Mg2+) and their clinical phenotype. Increased affinity for ATP is associated with ND; decreased affinity with CHI. In contrast, MgADP showed a weaker relationship. Diazoxide, known to reduce insulin release in some CHI cases, potentiates switching of CHI mutants from non-stimulatory to stimulatory states consistent with diazoxide stabilizing a nucleotide-bound conformation. The results emphasize the greater importance of nucleotide binding vs hydrolysis in the regulation of KATP channels in vivo.